Power-to-heat as a flexibility measure for integration of renewable energy. (1st June 2017) - Kirkerud, Jon Gustav; Bolkesjø, Torjus Folsland; Trømborg, Erik
Abstract: Higher shares of variable renewable energy (VRE) in energy systems reduce electricity spot prices at times when the supply of these sources are most abundant, leading to a lower market value per unit for these sources compared to energy sources with a constant or adjustable supply. This disadvantage for VRE can be offset by evolving the energy system towards wider market integration and flexible demand or supply. This study analyses how increased integration of heat and power markets by use of power-to-heat in district heating system could increase the value VRE sources in the Northern European power system. For the quantification, we apply a partial equilibrium model with a detailed representation of power and district heat generation for a likely 2030 energy system. The results show a markedly increase in VRE market value when installed capacity of power-to-heat is increased, especially in scenarios with a large Nordic power surplus. The study concludes that power-to-heat solutions in district heating systems can increase system flexibility in a short time perspective that considers hours to weeks, but also in a longer perspective that accounts for the significant inter-annual variability in hydropower supply. Highlights: Power-to-heat (P2H) has a potential of up to 19.1 TWh electricity in the Nordic energy system. Modelled P2H use is very limited in peak hours. Variable renewable energy are more competitive with high rates of P2H. Investments in P2H can represent a hedge against wet years and low CO2 prices.